(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2021)
In this work, we will try to analyze the factors and events of the social instability in Miguel Delibes’s Cinco horas con Mario. The social inequalities, materialized by a strong hierarchical organization, that prevent not only equality between people but also favor lot of injustice which make impossible members of society to live in harmony. Suddenly, these positive emotions are substituted for the mutual hate and stringent relations which cause, often, social exclusions and physical violence.